2022
DOI: 10.3390/agriculture12020271
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Use of Rhizobia to Mitigate Soil N2O Emissions

Abstract: Agriculture is a major anthropogenic source of the greenhouse gas N2O, which is also involved in stratospheric ozone depletion. While the use of rhizobial inoculants has already been reported as an emerging option for mitigating soil N2O emissions, this study presents an in situ abatement of 70% of soil N2O emission using the strain nosZ+ G49 vs. nosZ− USDA138 in association with soybean. Therefore, we consider that the choice of the inoculant strain of a leguminous crop should take into account the capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Among the researchers on this subject, [51] found that the substitution of conventional technology by inoculation technology in fava bean resulted in an average reduction in environmental impact of 19% per ha and 21% per ton; in pigeon pea, the average reduction was 12% per ha and 32% per ton. Similarly, [52] found that an insitu abatement of 70% of soil N 2 O emission using the strain nosZ+ G49 vs. nosZ− USDA138 in association with soybean. The development of elite rhizobacterial strains is necessary to maximize legume-specific symbiotic outcomes [51].…”
Section: Resultsmentioning
confidence: 84%
“…Among the researchers on this subject, [51] found that the substitution of conventional technology by inoculation technology in fava bean resulted in an average reduction in environmental impact of 19% per ha and 21% per ton; in pigeon pea, the average reduction was 12% per ha and 32% per ton. Similarly, [52] found that an insitu abatement of 70% of soil N 2 O emission using the strain nosZ+ G49 vs. nosZ− USDA138 in association with soybean. The development of elite rhizobacterial strains is necessary to maximize legume-specific symbiotic outcomes [51].…”
Section: Resultsmentioning
confidence: 84%
“…While N 2 O can be generated by multiple mechanisms, the only known biological sink for N 2 O is the reduction of N 2 O to dinitrogen by the enzyme N 2 O reductase (encoded by the nosZ gene) found in some denitrifying bacteria (Torres et al 2016 ; Minamisawa 2023 ). The nosZ gene has been detected infrequently in the rhizobia and has been found only in strains of the symbiotic species B. diazoefficiens (Sameshima-Saito et al 2006 ; Itakura et al 2013 ; Akiyama et al 2016 ), B. ottawaense (Wasai-Hara et al 2020a , b ), Ensifer meliloti (Bueno, et al 2015 ) and Rhizobium leguminosarum (Hénault et al 2022 ). Recently nosZ gene containing strains of the nitrogen-fixing soybean symbiont, B. ottawaense , were found to be highly efficient with regard to the reduction of N 2 O to inert dinitrogen gas and the use of these strains as inoculants was suggested as a strategy for mitigating N 2 O emissions from agricultural soils (Wasai-Hara et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that Ensifer melitoi , Rhizobium leguminosarum , and B. diazoefficiens possess nosZ -coding N 2 O reductase, and B. diazoefficiens may mitigate soil N 2 O emissions during the growth and post-growth periods of soybean crops on a field scale ( Itakura et al , 2013 ; Torres et al , 2014 ; Akiyama et al , 2016 ; Catherine et al , 2022 ). B. ottawaense was also recently shown to possess nosZ ( Mania et al , 2019 ; Wasai-Hara et al , 2020a ).…”
Section: Discussionmentioning
confidence: 99%